2004
DOI: 10.1016/j.femsec.2004.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, genetic diversity, temperature tolerance and toxicity of Cylindrospermopsis raciborskii (Nostocales, Cyanobacteria) strains from Thailand and Japan

Abstract: Cylindrospermopsis raciborskii is a planktonic, nostocalean cyanobacterium, which produces an alkaloid heptatoxin, cylindrospermopsin. We performed morphological observations, 16S rDNA sequence analysis, PCR fingerprint analysis of short tandemly repeated repetitive (STRR) sequences, temperature tolerances and toxin analysis to characterize 24 strains of this toxic cyanobacterium isolated from Thailand and Japan. All strains shared common morphological traits characteristic of C. raciborskii and showed high 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
73
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(79 citation statements)
references
References 15 publications
4
73
1
1
Order By: Relevance
“…The molecular analysis indicated that both morphotypes belong to the same species, corroborating previous studies employing different molecular markers in C. raciborskii (Saker et al, 1999;Wilson et al, 2000;Dyble et al, 2002;Chonudonkul et al, 2004). The extreme phenotype plasticity of C. raciborskii is reported by a number of authors and is related to both biotic and abiotic factors (Bouvy et al, 1999;Komarková et al, 1999;Shafik et al, 2003).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The molecular analysis indicated that both morphotypes belong to the same species, corroborating previous studies employing different molecular markers in C. raciborskii (Saker et al, 1999;Wilson et al, 2000;Dyble et al, 2002;Chonudonkul et al, 2004). The extreme phenotype plasticity of C. raciborskii is reported by a number of authors and is related to both biotic and abiotic factors (Bouvy et al, 1999;Komarková et al, 1999;Shafik et al, 2003).…”
Section: Discussionsupporting
confidence: 84%
“…This taxon exhibits extensive phenotype plasticity, with straight, sigmoid and coiled trichomes occurring in the same body of water (Bouvy et al, 1999;Komarková et al, 1999). Molecular studies have indicated that the different morphotypes of C. raciborskii should be considered as pertaining to the same species due to the high degree of genetic similarity (Saker et al, 1999;Wilson et al, 2000;Dyble et al, 2002;Chonudonkul et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…We also showed that differences in the transcription level of cyrA under different light intensities, and cyrK under different CO 2 conditions, have no control over the rates and timing of CYN pool size production. We therefore conclude that due to the constitutive nature of CYN pool size, the toxicity of a C. raciborskii bloom is likely to be controlled by population dynamics and strain-specific susceptibilities of strains (with different CYN cell quotas) to environmental parameters (21,33,(50)(51)(52)(53)(54)(55)(56) rather than by any direct stimulation of the CYN production pathway, including gene transcription. C. raciborskii bloom toxicity would also be governed by changes in light and CO 2 , which regulate the growth of (toxic) cells in the water column and the faster buildup of a (toxic) population, rather than by their effects on CYN pool size.…”
Section: Discussionmentioning
confidence: 92%
“…To date, there are no such data available in the literature concerning Cylindrospermopsis raciborskii. Some authors investigated the temperature effect at a single (fixed) irradiance and the influence of irradiance at a single (fixed) temperature for growth of strains of C. raciborskii originating from diverse areas (Shaker et al 1999;Shafik et al 2001;Briand et al 2004, Chonudomkul et al 2004Piccini et al 2011). However, the interaction of the range of light and temperature conditions on the growth of this invasive species is not described.…”
Section: Introductionmentioning
confidence: 99%